Investigation of SCOR Model in Connection with Performance and Warehouses - Pauluk, Júlia (International Journal of Engineering and Management Sciences, 2018)
Business leaders can use several strategic tools to improve the organization, depending on what they consider to be important. The Supply Chain Operational Reference Model (SCOR) is one of these. Its importance is to link business processes, performance metrics, best practices, and technology together and to create a unified structure. It promotes communication between the stakeholders of the supply chain and improves supply chain management and the efficiency of the related supply chain improvement activities. The aim of this study is to find out how the SCOR model appears in the international literature related to warehousing and performance. What methods and tools do authors use to investigate their research questions and hypotheses? Description statistics and category selection were used to present the results of the study. The number of SCOR model researches related to warehouse performance measurments are very rare, it is rather used to describe different processes. In the future, it would be worthwhile to extend the SCOR model analyzes to further fields, especially to warehouse performance measurements.